ESTIMATION OF DAILY MEAN AIR TEMPERATURE IN DISTINCT REGIONS OF BRAZIL USING ALTERNATIVE METHODS - JERSZURKI, Daniela; SOUZA, Jorge Luiz Moretti de (Scientia Agraria, 2010)
This study aimed to determine the reliability of two alternative methods (IAC and Max/Min) commonly used to estimate daily mean air temperature in relation to the standard method recommended by the National Institute of Meteorology (INMET). The air temperature data were obtained by the National Institute for Space Research (INPE), between the period 2005 to 2008 for twelve locations, in ten Brazilian States. Statistical analysis of data were made using linear regression and their correlation coefficients (R), precision index ("d") and performance index ("c"), considering INMET method as standard. The IAC method showed better results to estimate daily mean air temperature than Max/Min method for annual and seasonal period. The Max/Min method showed serious constraints to estimate the daily mean air temperature, especially in the spring and summer seasons. There was no influence of latitude and altitude on the performance of estimates daily mean air temperature with the IAC and Extremes methods for the localities studied.